Comprehensive analysis of vaginal microbiota in Chinese women with genital tuberculosis: implications for diagnosis and treatment - Zhan Zhang; Xiaonan Zong; Zhaohui Liu; Xiaoyu Dong; Huihui Bai; Linyuan Fan; Ting Li (BMC Microbiology)
Abstract Background Tuberculosis remains an infectious disease of global concern, with potential impacts on respiratory and intestinal microbiota owing to prolonged broad-spectrum antibiotic therapy. Despite its potential to cause infertility, the vaginal microbiota of women with genital tuberculosis remains poorly understood. We comprehensively analyzed the vaginal microbiota in Chinese women with genital tuberculosis. Results We recruited women with pelvic (n = 28), endometrial (n = 16), and pulmonary (n = 12) tuberculosis as the research group, and healthy women (n = 11) as the control group. Vaginal discharges were collected for metagenomic analysis of its microbiota. The alpha diversity of the vaginal microbiota in women with genital tuberculosis was slightly higher than that in healthy women, though the difference was not statistically significant (P = 0.23). Similarly, no significant differences in alpha diversity were observed between women with genital and pulmonary tuberculosis (P = 0.82) or between those with pelvic and endometrial tuberculosis (P = 0.82). Notably, the lowest alpha diversity was recorded six months to one year after initiating anti-tuberculosis treatment, with this decline being statistically significant (P = 0.023). The dominance of Lactobacillus iners in the vaginal microbiota was more common in women with genital tuberculosis than that of Lactobacillus crispatus. Furthermore, the abundance of short-chain fatty acid -producing anaerobes, such as Actinomycetes, Streptococcus, and Finegoldia, were significantly increased. Short-chain fatty acid precursor pathways, including the ko03010 ribosome pathway, ko00970 aminoacyl-tRNA synthesis, ko00230 purine metabolism, ko00240 pyrimidine metabolism, and ko00010 glycolysis gluconeogenesis pathway, were significantly upregulated in women with endometrial tuberculosis. Conclusions Extrapulmonary tuberculosis, particularly genital tuberculosis and its associated vaginal dysbiosis impacts female fecundity. Vaginal dysbiosis is more pronounced when M. tuberculosis invades the endometrium. Given the effect of antibiotics on vaginal flora, probiotic combined interventions could be used as a future research direction. Clinical trial number Not applicable.